Ipsilateral Medial and Lateral Discoid Meniscus with Medial Meniscus Tear - Shimozaki, Kengo (J Orthop Case Rep, 2016)
INTRODUCTION: Discoid meniscus is a well-documented knee pathology, and there are many cases of medial or lateral discoid meniscus reported in the literature. However, ipsilateral concurrent medial and lateral discoid meniscus is very rare, and only a few cases have been reported. Herein, we report a case of concurrent medial and lateral discoid meniscus. CASE REPORT: A 27-year-old Japanese man complained of pain on medial joint space in his right knee that was diagnosed as a complete medial and lateral discoid meniscus. In magnetic resonance imaging, although the lateral discoid meniscus had no tear, the medial discoid meniscus had a horizontal tear. Arthroscopic examination of his right knee similarly revealed that the medial discoid meniscus had a horizontal tear. In addition, the discoid medial meniscus also had an anomalous insertion to the anterior cruciate ligament, and there was also mild fibrillation of the medial tibial cartilage surface. We performed arthroscopic partial meniscectomy for the torn medial discoid meniscus but not for the asymptomatic lateral discoid meniscus. The latest follow-up at 18 months indicated satisfactory results. CONCLUSION: We report a rare case of ipsilateral medial and lateral discoid meniscus with medial meniscus tear. The medial discoid meniscus with tear was treated with partial meniscectomy, whereas the lateral discoid meniscus without tear was only followed up.